2012
DOI: 10.1080/09540121.2011.648161
|View full text |Cite
|
Sign up to set email alerts
|

Sexual life, options for contraception and intention for conception in HIV-positive people on successful antiretroviral therapy in Thailand

Abstract: This article reports on the sexual life of HIV-positive heterosexual men and women in a stable relationship and on successful antiretroviral therapy in Thailand. We focused on one side on their sexual practices and options for contraception, and on the other on their intention for conception and factors influencing it, in the time of highly active antiretroviral therapy. In a cross-sectional study, 200 participants completed a questionnaire. Eleven female participants took part in focus group discussions (FGD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, continuous professional development in the area of sexual and reproductive health should be made available to health care providers caring for adolescents and young women [ 41 ]. In this study, majority of the adolescents who used family planning used short-term methods of family planning which we mainly explain as owing to misconception about the method among health care providers [ 43 45 ]. In Uganda, majority of women are offered all major modern contraceptive methods at public health facilities [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, continuous professional development in the area of sexual and reproductive health should be made available to health care providers caring for adolescents and young women [ 41 ]. In this study, majority of the adolescents who used family planning used short-term methods of family planning which we mainly explain as owing to misconception about the method among health care providers [ 43 45 ]. In Uganda, majority of women are offered all major modern contraceptive methods at public health facilities [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have considered intention as an immediate driver of certain behaviors such as smoking [31][32][33], sexual activity, contraception use, abortion [34][35][36][37], illicit drug use [38][39][40], and childbearing [41][42][43].…”
Section: The Literature On Migration Intentionsmentioning
confidence: 99%
“…Those who do not wish to become pregnant can be supported to access and use contraception. Though fertility desire may increase for some women after starting ART, recent data suggest that on average HIV-infected women tend to want fewer children than HIV-uninfected women [19, 20, 21*]. In one study, HIV status was the firmest predictor of not wanting future children [21].…”
Section: Fertility Intentions Family Planning Use Unintended Pregnamentioning
confidence: 99%
“…Drivers for not desiring children include fear of adverse health effects on the mother, fear of transmission to the child or to a partner, degree of knowledge about PMTCT interventions and their efficacy, financial hardship, community or provider stigma, death of a child, current ill health, leaving child an orphan, and having `enough' children [2125]. Alternatively, desire for children among HIV-infected individuals is associated with having no or few children, partner's desire for children, awareness of and access to ART, being married few years, and higher education [19, 23, 25, 26]. Two studies showed a significantly higher desire for children among HIV-infected men than women [25**, 27].…”
Section: Fertility Intentions Family Planning Use Unintended Pregnamentioning
confidence: 99%
See 1 more Smart Citation